Fast X‐ray microfluorescence imaging with submicrometer‐resolution integrating a Maia detector at beamline P06 at PETRA III. (18th October 2016) - Boesenberg, Ulrike; Ryan, Christopher G.; Kirkham, Robin; Siddons, D. Peter; Alfeld, Matthias; Garrevoet, Jan; Núñez, Teresa; Claussen, Thorsten; Kracht, Thorsten; Falkenberg, Gerald
Abstract : The integration of a Maia detector in the Microprobe setup of beamline P06 at the storage ring PETRA III at the Deutsches Elektronen‐Synchrotron (DESY) in Hamburg, Germany, is described. The Maia detector is an advanced imaging scheme for energy‐dispersive detection and the analytical performance at the beamline is characterized and examples from key applications are provided. Abstract : The high brilliance of third‐generation synchrotron sources increases the demand for faster detectors to utilize the available flux. The Maia detector is an advanced imaging scheme for energy‐dispersive detection realising dwell times per image‐pixel as low as 50 µs and count rates higher than 10 × 10 6  s −1 . In this article the integration of such a Maia detector in the Microprobe setup of beamline P06 at the storage ring PETRA III at the Deutsches Elektronen‐Synchrotron (DESY) in Hamburg, Germany, is described. The analytical performance of the complete system in terms of rate‐dependent energy resolution, scanning‐speed‐dependent spatial resolution and lower limits of detection is characterized. The potential of the Maia‐based setup is demonstrated by key applications from materials science and chemistry, as well as environmental science with geological applications and biological questions that have been investigated at the P06 beamline.